A STUDY ON SAMANYAM VRUDDHI KARANAM WITH REFERENCE TO MUKTASHUKTI PISHTI IN ASTHI KSHAYA - PV, *Arpana; Yaligar, MG. (International Journal of Ayurveda and Pharma Research, 2016)
Asthikshaya is a state where the functional capacity of Asthi (bone) is compromised due to the decrease in its Guna (properties) Karma (function) and structure of Asthi. Asthikshaya is correlated to osteopenia/ osteoporosis in contemporary science. Osteopenia/osteoporosis is a major global health problem affecting females at an average age of 50 making their bones susceptible to fracture. 1 out of 3 females in India suffer from osteopenia/osteoporosis making it a burning problem in present era. This has led to tremendous interest in Ayurvedic alternatives. Ayurveda states decrease of any entity in the body should be increased by administering similar entity by the means of food or activity. This treatment is based on Samanya (similarity) where Samanya is the cause for Vruddhi (increase in its properties and functional capacity). 30 female subjects between the age of 45 to 65, were included in a single group study by purposive consecutive sampling method, were administered with Muktashuktipishti 250mg 2 capsules per day with lukewarm water before food for a period of 2 months. Subjects were assessed pre intervention, during and post intervention. Obtained results were subjected to appropriate statistical analysis to see the significance. By the result it is noted that Muktashukti is Gunasamanya (Sthira, Sthula, Katina, and Sandragunas) to Asthi thus increases Asthi in Asthikshaya with improvement in Kesha (hair fall), Nakha (breakage of nails) Dantashadana (loosening of teeth), Shrama (tiredness) and Asthitoda (pain in bony area) and statistically significant.